KEWIRASWASTAAN DALAM PERSPEKTIF TEORITIS - Joko Widodo (Economic Education, University of Jember, 2016)
Entrepreneurship is a profession/work performed by a person professionally in the field of business/ business. Entrepreneur is someone who has a positive mental attitude, so enterprising above its own merits. Entrepreneurship and Self is the sense of the term foreign Indonesia Entrepreneurship and Entrepreneur. Mental attitude of self-employed as a tendency within an entrepreneur to behave entrepreneurship in the business world in response to objects by basing ourselves on the knowledge and feelings about the values of entrepreneurship. The values of entrepreneurship that include (a) had the idea/ideas, (b) had the initiative/initiatives, (c) have the inventiveness/creativity, (d) have confidence in yourself, (e) have a clear purpose in life , (f) have the courage to face risks, (g) always work together, (h) is not inferior/shame, and (i) have the entrepreneurial skills and salesmanship.Keywords: Entrepreneurship, Theoretical Perspectives